ANALISIS PENGARUH MODAL DAN TENAGA KERJA TERHADAP EFISIENSI PRODUKSI GENTENG DI DESA SUKOREJO KECAMATAN GANDUSARI KABUPATEN TRENGGALEK - Happylya Ulfa Agustin; Wahyu Hidayat Rianto; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
Aims to determine and analyze the influence of factors of production capital and labor to the production of tile and efficiency of the production of tiles in the village Sukorejo Gandusari District of Trenggalek. The research method used in this study is quantitative which begins with setting up model and test models made. The model and links between those independent and dependent, where independent variable made up of capital and labor while dependent variable is the production of tiles. The sample was done by using accidental sampling. The analysis used are the assumptions of classical, the analysis of the regression of the linear risks using the production Coob-Douglas, the statistics analysis and effeciency of the production of tiles. The test results of a partial to show that labor have a significant effect on the tiles. The capital didn’t have a significant effect on the tiles. The test model simultaneously shows that labor and capital have a significant effect on the tiles. Then the results of the efficiency of business production obtained figures of 2,466 the meaning of the business plate is an efficient.Keywords: Tile Industries, Factors of Production, The Efficiency of Production, The Production.